Use o fDulbecco's modified eagle's medium DMEM/F12 HAM for Marek's disease virus cultivation in chicken embryo fibroblasts - Ye. Yu. Khanyukova; M. A. Shustova; H. Ye. Kamalova (Ветеринария сегодня)
The opportunity of using Dulbecco's Modified Eagle's Medium DMEM/F12 Ham for Marek's disease cultivation in chicken embryo fibroblasts was studied. It was determined that if appropriate virus cultivation parameters are chosen the abovementioned medium enables to prepare virus material with high agent infectivity.